Clinical Outcomes of Mid-Urethral Sling Procedures for the Treatment of Female Urinary Incontinence: A Retrospective Cohort Study - Marwah Alatawi; Dania Bresali; Lateefa AlDakhil; Hazem Al-Mandeel; Abdulrahman Bogis; Ghadeer Al-Shaikh (IMR Press, 2024)
Background: Urinary incontinence (UI) significantly affects women's quality of life globally. Mid-urethral sling (MUS) procedures are common minimally invasive surgeries for treating stress urinary incontinence (SUI) and mixed urinary incontinence (MUI), but comparative outcome studies, especially regarding complication rates, are lacking. The purpose of this study was to assess and compare the efficacy and safety of the retropubic tension-free vaginal tape (TVT) and transobturator tape (TOT) approaches in treating SUI and MUI. The study also aimed to investigate predictive factors for intraoperative and postoperative complications. Methods: A retrospective cohort study was conducted at King Saud University Medical City from February 2016 to October 2022, involving 166 women who underwent either TVT or TOT surgeries. Data were collected on intraoperative and postoperative complications, with statistical analyses performed using chi-square tests and multivariate regression to identify significant predictors of morbidity. Results: The study included 166 patients who underwent MUS procedures, with 61% (n = 102) undergoing retropubic TVT and 39% (n = 64) undergoing TOT surgeries. The demographic characteristics were similar between the groups, with no significant differences in age (p = 0.559), body mass index (BMI) (p = 0.600), or presence of cystocele (p = 0.912). The TVT group experienced a significantly higher rate of intraoperative bladder/urethral perforation compared to the TOT group (9.8% vs. 0%, p = 0.008). Early postoperative complications, including urinary retention, were comparable between the groups (TVT: 10.8%, TOT: 12.5%, p = 0.600). Patients in the TOT group had shorter hospital stays, with 71.9% discharged within one day compared to 41.2% in the TVT group (p < 0.001). At long-term follow-up (>6 months), both groups reported high satisfaction, with 93.7% of TVT and 87.3% of TOT patients reporting good or very good comfort (p = 0.252). However, pain-free status was significantly higher in the TVT group (91.1% vs. 67.2%, p < 0.001). Both retropubic and transobturator MUS techniques are effective for managing SUI, with the transobturator approach showing fewer complications and shorter recovery times. Conclusions: Both retropubic and transobturator MUS techniques are effective for managing SUI, with the transobturator approach showing fewer complications and shorter recovery times. We recommend the formation of a national registry to track long-term outcomes and enhance procedural evidence.